Can the Hypnoteaching Method Increase Students’ Speaking Ability? - Dian Lestari; Abdullah Syarif (Elsya, 2020)
The objective of this research was to invest the effect of implementation of hypnoteaching toward eleventh grade to increase students’ speaking ability. The research was facused to know the significant effect of implementation hypnoteaching method at MA YASMI DURI. The population are 42 persons of eleventh grade that consists of two classes and the sample are 16 persons of IPA 1 Class. The research design was pre-experiment with pre-test and post-test design. The are two variables, they are hypnoteaching method and speaking ability, and then to analyze the data obtained,the research used Paired sample T-test.